EMPLOYEE RETENTION AND TALENT MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Aliaa Diyana Zamri; Siti Noorjannah Abd Halim (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This systematic literature review (SLR) utilises the PRISMA framework to study the research on employee retention and talent management, focusing on articles published between 2022 and 2024 in Scopus and Web of Science databases. Key themes such as retention, attraction and learning development are synthesised across various sectors and regions. The review has addressed the research question: “How do various talent management strategies influence employee retention across industries and regions?”. A total of 15 studies were selected following a comprehensive search and screening process. This review highlights the significance of data-driven retention strategies, work-life balance, and generation demands and provides practical implications for managers and HR professionals. Recommendations for future research include investigating the growing role of sustainability in talent management especially in the 21st century.